P-004 Endovascular management of acute ischemic stroke based on perfusion studies: a single center experience. (12th July 2011) - Sharma, J; Shams, T; Blackham, K; Hsu, D; Tarr, R; Sunshine, J
Abstract : Background: CT Perfusion or MR perfusion studies are often used to evaluate patients who presents with Acute Ischemic Stroke (AIS). Little published data are available regarding the real-time use of perfusion imaging to guide endovascular management. Objective: To evaluate the role of perfusion imaging in selection and decisions for endovascular management in AIS patients. Methods: Retrospective chart review was performed from prospectively collected database of patients with AIS who were treated with endovascular therapy from April 2010 to December 2010. Patients were divided into two groups: Group 1: included 23 patients who had initial perfusion study performed to decide endovascular management by exclusion of candidates with large matched defects, 10 males and 13 females with mean age of 68.13 (range 39–86), mean NIHSS 16.4 (range 6–26) and Group 2: included 21 patients who were treated with endovascular management without perfusion imaging screening, 10 males and 11 females with mean age 64.86 (range 34–89), mean NIHSS 15.7 (range 0–42). The primary outcome measures following the intervention were intracranial hemorrhage rate and mortality rate. Results: Group 1: All patients had lesions in the anterior circulation. Four patients received a combination of IV and IA tPA. Two received intravenous tPA, two received intra-arterial tPA. MERCI was used in seven patients and Penumbra device was used in seven patients. Post procedure hemorrhage was 13% (n=3). The mortality rate was 4.3% (n=1). Group 2: 15 patients had lesions in the anterior circulation and six patients in posterior circulation. Four patients received a combination of IV and IA tPA. Three received intravenous tPA, six received intra-arterial tPA. MERCI was used in eight patients and Penumbra device was used in 14 patients. Post procedure hemorrhage was 30% (n=6). The mortality rate was 24% (n=5). Conclusions: Although not a matched population, we note a trend toward a lower rate of symptomatic hemorrhage and mortality in patients who were selected based on perfusion study for endovascular therapy. Further prospective trials are warranted to evaluate role of perfusion based studies in selecting patients for endovascular management.